Oil Industry as a Factor in the Expansion of the Transport Infrastructure of the Volga-Caspian Region in the Last Third of the 19th - Early 20th Century - Eshchenko, Yuliya G. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
In their study, the author considers the influence of the Russian oil industry on the development of the VolgaCaspian transport corridor in the last third of the 19th - early 20th century. Within their text, they illustrate that in the postreform period, due to the emergence of a free labor market, an opportunity arose for the development of entrepreneurship and entrepreneurial initiative. Based on a set of legislative documents and archival materials, some of which are introduced into scientific use for the first time, the author characterizes the main directions of the state policy in the oil industry in the period under study. They reveal in their text the interdependence between oil production volumes and the rapid development of the ports of the VolgaCaspian transport corridor, and the influence of scientific and technological progress on the successful development of the oil industry. In addition, the logistics infrastructure of the region is assessed as well as the changes in the territorial and transport structure of the VolgaCaspian transit route in the last third of the 19th - early 20th century. Within the framework of the theory of organizational and economic mechanisms, the author comes to the conclusion that the modernization processes in the oil industry in the last third of the 19th - early 20th century contributed to a positive transformation and complication of the infrastructure of the VolgaCaspian region. This transformation was expressed in the rapid development of new types of transport and the creation of new transport routes, a change in the range of goods in traditional cargo turnover, and an increase in the economic profitability of both transport and freight traffic. In addition, the expansion of markets for goods and the beginning of the merging of oil production and trade and transport capital and their participation in the development of strategically important sectors of the economy showed the benefit of this transition.